Histological Studies on the Non-Osseous component of the Hard Palate in Domestic Pig (Sus scrofa domesticus) - Damini V; Prasanth Babu A; Santhi Lakshmi M; Bharathi S; Sharon Nancy Nikhila K.P; Raja K; Supriya B; Kalyan Chakravarthy M (Indian Journal of Veterinary Anatomy, 2026)
The bony palate along with the mucosa covering its oral surface together constitutes the hard palate. The microanatomical studies of the non-osseous component of the hard palate showed the keratinized stratified squamous epithelium and propria-submucosa. The propria-submucosa was composed of dense irregular connective tissue containing collagen and reticular fibers, adipose tissue, smooth muscle cells, nerve fibers, blood vessels, capillary plexuses, lymphatic vessels and connective tissue cells like lymphocytes, fibroblasts and fibrocytes. The highest vascularity was observed at the papilla incisiva level, where the nasopalatine duct and plate-like hyaline cartilage surrounded by a perichondrium were also present. Notably, no glands were observed at any level of the non-osseous component of the hard palate in domestic pigs.